EFL Students’ Perceptions on the Use of TikTok in Improving Speaking Skill - Farisca Adhani, Olivia; Nur Fadhillah, Aisyah; Auliya Yahya, Roza; Wintolo, Tri (English Education:Journal of English Teaching and Research, 2023)
Currently, many different methods are being used to learn English as it occurred today, combining a variety of media or applications, including TikTok videos. Different student attitudes emerge as a result of the possibility of studying English through Tiktok videos. This study aims to investigate students' opinions and the difficulties they encounter when using TikTok videos to hone their speaking abilities. Descriptive qualitative method was employed in this study. Nine students from one reputable Islamic private senior high school in Bekasi, West Java were served as the study's subjects. Since some students were discovered using tiktok videos to practice English, the nine participants were selected and considered qualified for data collection through interview. Based on the result of this study, students had an assortment of perspectives on using TikTok videos to learn English, both favorable and unfavorable ones. Further, utilizing TikTok videos for teaching English to students presented a number of difficulties. Confirming to the results of this study, students had both advantageous and negative opinions on utilizing TikTok videos to learn English. Additionally, there were several kinds of difficulties that arose when students utilized TikTok short clips to study English.